THE INFLUENCE OF WOMEN'S INVOLVEMENT ON THE HUMAN DEVELOPMENT INDE IN THE COASTAL AREAS OF INDONESIA (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
ABSTRACTDevelopment in Indonesia's coastal areas is challenging, with a variety of factors affecting the welfare of its communities. Women's involvement and socio-economic factors are important in formulating inclusive and sustainable development policies. This study aims to identify and analyze the influence of women's involvement and socio-economic variables, including women's income contribution, women's average years of schooling, women's labor force participation rate, women's involvement in parliament, gender inequality index, population, and number of poor people, on the Human Development Index (HDI) in Indonesia's coastal areas. The data analysis method used was a multiple linear regression approach. Secondary data were obtained from various sources. Data collection was conducted through surveys and documentation analysis.The results show that women's involvement has a significant influence on HDI in coastal Indonesia. Women's income contribution, women's labor force participation rate, and women's average years of schooling have a significant positive influence on HDI. On the other hand, gender inequality index and poverty headcount have a significant negative impact. These findings provide a deeper understanding of the factors that influence human development in Indonesia's coastal areas and provide a basis for formulating more effective policies to improve the welfare of coastal communities.
Keywords: Human development index; female labor participation rate; gender inequality index